Needs Analysis for the Development of an Assessment Rubric for Writing Explanatory Texts Among Grade 5 Primary School Students - Rosmawati , Erma; Apriliya, Seni; Yusuf Muslihin, Heri (Papanda Publisher, 2025)
This research is motivated by the unoptimal practice of writing assessments of explanatory text in grade V elementary school, which tends to be subjective and lacks specific feedback. This study aims to analyze the need to develop an assessment rubric for writing explanatory texts based on the characteristics of grade V students. The research method used is qualitative, with data collection through observation of assessment practices in the classroom, in-depth interviews with grade V teachers, and review of documentation related to writing assessment. The results showed that current assessment practices vary, use implicit criteria, and provide general feedback. Teachers acknowledge difficulties in assessing specific aspects of writing explanatory texts and need more objective instruments, such as rubrics. Analysis of curriculum documents and existing assessment instruments showed a lack of criteria specification for explanatory texts. The literature study supports the urgency of developing specific, clear, measurable, holistic, and practical rubrics and their potential as assessment and learning tools. This study concludes that there is a significant need to develop a writing assessment rubric for explanatory texts suitable for grade V to improve the objectivity of assessment, feedback effectiveness, and writing learning quality.